2-Deoxy-D-glucose and combined 2-Deoxy-D-glucose/albendazole exhibit therapeutic efficacy against Echinococcus granulosus protoscoleces and experimental alveolar echinococcosis. - Qi Xin; Wei Lv; Yunxi Xu; Yumei Luo; Caifang Zhao; Bichen Wang; Miaomiao Yuan; Huanping Li; Xiaoxia Song; Tao Jing (Public Library of Science (PLoS), 2022)
2-Deoxy-D-glucose (2-DG) is a glucose analog used as a promising anticancer agent. It exerts its effects by inhibiting the glycolytic energy metabolism to deplete cells of energy. The larval stage of Echinococcus relies on glycolysis for energy production. Therefore, in this study, we investigated the in vitro and in vivo efficacy of 2-DG against the larval stage of Echinococcus granulosus and E. multilocularis. 2-DG exhibited significant time- and dose-dependent effects against in vitro cultured E. granulosus protoscoleces and E. multilocularis metacestodes. A daily oral administration of 500 mg/kg 2-DG in E. multilocularis-infected mice effectively reduced the weight of metacestodes. Notably, the combination treatment, either 2-DG (500 mg/kg/day) + albendazole (ABZ) (200 mg/kg/day) or 2-DG (500 mg/kg/day) + half-dose of ABZ (100 mg/kg/day), exhibited a potent therapeutic effect against E. multilocularis, significantly promoting the reduction of metacestodes weight compared with the administration of 2-DG or ABZ alone. Furthermore, the combination significantly promoted apoptosis of the cells of metacestodes and inhibited glycolysis in metacestodes, compared with the administration of 2-DG or ABZ alone. In conclusion, 2-DG exerts an effective activity against the larval stage of Echinococcus. Thus, it may be a promising anti-Echinococcus drug, and its combination with ABZ may provide a new strategy for the treatment of echinococcosis in humans.